Compartilhamento de imagens nas redes sociais digitais: reflexões acerca da autoexposição do corpo de adolescentes no Instagram - Sousa, Wanessa Ferreira de (2022)
This dissertation aims to understand the nuances present in the sharing of adolescent body images on digital social networks, analyzing the production/reproduction/consumption relations of capitalism in the face of this reality and also seeking to understand its consequences. For this, we used Dialectical Historical Materialism as an epistemological matrix, with a quantitative-qualitative approach of a descriptive and transversal character, using as an investigation procedure the application of online questionnaires and a netnography on Instagram. Our sample had 44 participants, students of the 3rd year of Integrated High School from a campus of the Instituto Federal de Goiás. Thus, the work was structured in 3 chapters that sought to understand: the scenario through categories such as Work, Culture, Education and Vocational Education in Brazil; the context by the categories Body, Cultural Industry, Digital Social Networks; and the research bringing the Self-exposure of the Body of adolescents. The results showed that digital social networks, in addition to allowing communication between people, have also become a place of body exposure, showing us that visibility has become a way of producing oneself that meets standards expected by spectators, even bringing consequences in the formation of adolescents' subjectivity.